Epithelial-stromal transition of MMP-7 immunolocalization in the rat ventral prostate following bilateral orchiectorny - Felisbino, Sergio L.; Justulin, Luis A.; Carvalho, Hernandes F.; Taboga, Sebastiao R. (Elsevier B.V., 2007)
Epithelial cells from involuting rat ventral prostate (VP) express Matrilysin (MMP-7) mRNA. Herein, we investigated by immunohistochemistry the NIMP-7 protein location and its association with tissue changes following castration in the VP. Normal and castrated adult male Wistar rats were sacrificed at different times after surgery. VP was examined by immunocytochemistry and immunoprecipitation. Castration promoted a shrinking of prostate ducts with an extensive stromal remodeling. In the VP from normal rats, MMP-7 immunoreactivity was found in epithelial secretory granules. Three days after castration, immunostaining for MMP-7 was found in both the epithelial secretory granules and in the stroma just below the epithelium, mainly at the distal ductal tips. At seven and 21 days after castration, the immunostaining for MMP-7 was found only in the stromal space. Immunoprecipitation confirmed the specificity of the primary antibody by rescuing a pro-enzyme form (28 kDa) in the prostate extracts. The present results suggest that MMP-7 participates in the epithelial-stromal interface remodeling of the ventral prostate during the involution achieved by castration, probably in the degradation of components of the epithelial basement membrane. (c) 2007 International Federation for Cell Biology. Published by Elsevier Ltd. All rights reserved.
Keywords: metalloproteinases; basement membrane; castration; matrilysin; collagen fibers; stroma